Pertanggungjawaban Pidana Terhadap Anak Sebagai Orang Yang Membantu Melakukan Tindak Pidana Pembunuhan Berencana : Studi Putusan Pengadilan Negeri Siak Nomor 05/Pid.Sus.Anak/2014/Pn.Siak. Jo Putusan Pengadilan Tinggi Pekanbaru Nomor 01/Pid.Sus/Anak/2014/P - Immanuel Colia; Madiasa Ablisar; Muhammad Hamdan; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
Abstract. Criminal act of premeditated murder is an action intentionally done by one or more persons by initially planning to take other person’s life. The premeditation includes the certain time period in which a person thinks peacefully and makes the decision to take another person’s life. An action can be called a premeditated murder under one condition is that the action has firstly been premeditated (taking one person’s life). Nowadays premeditated murders are not done by adults alone, but in same legal cases, they involve minors to help them. Children in conflict with law are called juvenile criminals, although a child has helped a premeditated murder, he cannot absolutely be held responsible for the crime that he did. It firstly has to be proved whether his action meets the elements of a criminal act pursuant to the articles Stipulated in Penal Code. If his action does not meet the required elements, the child cannot be held responsible. He might have forcibly helped committing the premeditated murder or been influenced by force such as inevitable threats from adults. In other words, a child’s involvement is only used as a tool to carry forward adults’ bad intentions. Keywords : premeditated murder, children, penal sentence.